The Impact Parameters of the Broadening and Shift of Spectral Lines - Roston, G. D.; Helmi, M. S. (Biological Sciences - PJSIR, 2005)
. The classical theory of collisional broadening and shift coefficients (b, d) of an isolated spectral line was used to obtain simple analytical formulae for calculating both b and d. These formulae were obtained on the assumption that the short range interaction was effective only in the broadening, while the long range was effective in the shift of the spectral line. These coefficients, b and d depended on the limiting phase shifts responsible for broadening h0b and shift h0d. It was found that the values of h0b and h0d were not equal to each other, as was proposed by Weisskopf h0b = h0d = 1, but were instead hob = ± p / 5 and hod = ± p / 2. The correct signs of these phases were obtained and defined. When these phases were applied with their correct signs in the approximate formulae, the broadening bc and shift dc coefficients for some interactions of Tl, Hg, Cd, Zn, Ar and Ne with inert gases and self-interactions were in agreement with the corresponding values obtained numerically by other authors. The limit at which the shift changed its sign was also obtained. New impact parameters which were not known up to now have been discussed and obtained.